Pengaruh transformational leadership terhadap psychological well-being melalui job satisfaction dan employee engagement pada karyawan di perusahaan manufaktur - Putri, Amelia Arwidya; Nugrohoseno, Dwiarko (Universitas Negeri Surabaya, 2025)
This study aims to test and analyze the effect of transformational leadership on psychological well-being through job satisfaction and employee engagement on employees. The approach used in this study is quantitative. The sampling technique used saturated sampling with a total of 44 employees. The data in this study were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 4.1.0.6 software. The results of the study indicate that transformational leadership has a positive effect on psychological well-being, transformational leadership has a positive effect on employee engagement, employee engagement has a positive effect on psychological well-being, employee engagement mediates the relationship between transformational leadership and psychological well-being, transformational leadership has a positive effect on job satisfaction, job satisfaction does not have a positive effect on psychological well-being, job satisfaction does not mediate the relationship between transformational leadership and psychological well-being, employee engagement does not have a positive effect on job satisfaction, job satisfaction and employee engagement do not mediate the relationship between transformational leadership and psychological well-being. This research implies the need for company to increase focus on psychological well-being by strengthening transformational leadership and employee engagement.